Stigma Rasisme Kulit Putih Terhadap Kulit Hitam sebagai Budak dalam Kemasan Sereal Kellogg’s - Lazuardian, Arga; Risqullah, Alif (Borobudur Communication Review, 2023)
Advertising serves as a means for prominent corporations to uphold their brand image. Racism can arise due to inadequate media utilization and a lack of advertising understanding, as Kellogg's Cereal exemplified in their 2017 advertisement "Ninja Corn Pop." Kellogg's cereal, which primarily caters to youngsters, inadvertently instills racial bias in young minds. This study aims to substantiate black individuals' systemic discrimination in various industries. This research aims to offer valuable insights and empirical evidence to stimulate critical thinking and serve as a foundation for future investigations into the pervasive issue of racism within the rapidly expanding consumer products industry